If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + 7i) + -1(-6 + -1i) = 0 Remove parenthesis around (7 + 7i) 7 + 7i + -1(-6 + -1i) = 0 7 + 7i + (-6 * -1 + -1i * -1) = 0 7 + 7i + (6 + 1i) = 0 Reorder the terms: 7 + 6 + 7i + 1i = 0 Combine like terms: 7 + 6 = 13 13 + 7i + 1i = 0 Combine like terms: 7i + 1i = 8i 13 + 8i = 0 Solving 13 + 8i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 8i = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 8i = 0 + -13 8i = 0 + -13 Combine like terms: 0 + -13 = -13 8i = -13 Divide each side by '8'. i = -1.625 Simplifying i = -1.625
| 7x-11=-109 | | 59=-4s+8 | | 6+3(5x-6)=6-4(2x+1) | | 3b^0.5(2b^0.5+5b^3/2) | | -14+6x+7=2x+1+5x | | by=a+x | | yb=x+a | | -2(7x-1)+7=-14x+9 | | (4+9i)+(5-8i)= | | 3(4x-2)=-2(-6x+3) | | 10m^2=2m+3.14159 | | 8=-7x+4+2 | | 2(15d+45c)+5/6(12d+18c) | | 5*-1+4*5= | | 16=4x-5 | | -2k^2+72=0 | | y-12=0.666(x-6) | | -4x-1/2y=10 | | -7=4r | | 3c-2d=2 | | 3/4x-5-7/3x-1 | | 3b^1/2(2b^1/2+5b^3/2) | | 5(2x+8x)=0 | | 3x+5=12x-20 | | 3=2c-11 | | -d+-18=0 | | 1566-853= | | x*13+15=x*5+207 | | 3x-2/7=-45 | | 3.42-6.3x+1.11=22.8 | | -77-7x=9x+15 | | -2(3x+4)-2=12x-6(3x+2) |